Wastewater irrigation: past, present, and future - Zhang, Yucui; Shen, Yanjun (Wiley interdisciplinary reviews. Water, 2019)
With population growth and social and economic development, water shortage is becoming a serious issue worldwide. As a key alternative water resource, wastewater can be used in agriculture to compensate for water shortages. Wastewater irrigation has a long development history and has undergone different phases in developing and developed countries. Untreated wastewater irrigation can come with numerous environmental problems. Strong management practices, such as the application of suitable treated and irrigated technologies, can be used to reap substantial benefits while minimizing risks. We discussed the major challenges associated with wastewater irrigation and its future use to help improve wastewater irrigation practices around the world. This article is categorized under: Engineering Water > Sustainable Engineering of Water Engineering Water > Water, Health, and Sanitation Wastewater irrigation began with the water shortage, fertilizer saving or preventing water pollution centuries ago, developed with the technological innovations, and still faces many challenges in the future. This is a broad and systematic overview of the history, the present status and the challenges in future focused on wastewater irrigation.